Kekosongan Hukum CSR (Corporate Social Responsibility) Yang Berasal Dari Donasi Konsumen Minimarket - Lailawati, Fadilla Dwi (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2022)
CSR is a manifestation of the company's concern for the economy, social and environment. CSR is funds that should be issued by companies for contributions from companies for social, but nowadays many entrepreneurs, especially minimarkets ask for change for these charitable activities, to carry out these CSR activities, how this happens is still a problem in society because it has not There are also strict rules, when a company, especially a minimarket-based company, carries out CSR for social activities through funds from consumer donations, instead of asking for change for social activities. Rules regarding this matter are also still a legal vacuum (vacum of norm), so that punishments for minimarket or supermarket companies who commit fraud by using funds from consumers for their CSR do not receive strict action or sanctions, because basically in the field there are so many companies. which takes shelter in the minimarket sector that uses this method for its CSR funds